Production of recombinant 503 antigen of Leishmania infantum chagasi using cultivation in batch and fed-batch - Santos, Everaldo Silvino dos (2014)
Visceral leishmaniasis is an infecto-parasitarian disease caused by obligatory intracellular protozoa belonging to the genus Leishmania, and might be lethal since there is no precocious diagnosis and proper treatment. Despite the considerable effort, there is no effective and safe vaccine for human use [1]. Genetically modified micro-organisms are used industrially in general for production of hormone, antibiotics and proteins. In the production of heterologous molecules, both the expression and the production step are important [2]. Therefore, the study of cultivation conditions in bioreactor plays an important role for the process viability of batch and fed-batch [3]. Thus, the aim of this work was to study strategies for production of the 503 antigen of Leishmania infantum chagasi using cultivation in batch and fed-batch